Understanding Interactions at Science Centers and Museums Approaching Sociocultural Perspectives - Davidsson, Eva.; Jakobsson, Anders; SpringerLink (Online service) (Rotterdam : SensePublishers, 2012)
There is an increasing interest in understanding learning and knowledge development when visitors attend informal institutions, such as museums, science centers, aquariums and botanical gardens. But in what ways do visitors develop new knowledge, skills and awareness about displayed issues in these kinds of settings and how does the exhibition environment affect and scaffold learning processes? In this book, the authors turn their attention to visitors$1 (Band staff members$1 (Bactions and dialogues during the visits in order to identify and study learning situations. A common approach is the use and development of socio-cultural and cultural-historical frameworks and theories as means for coming closer to the significance of interactions at different levels and in different contexts. The individual chapters cover learning interactions in relation to staff members$1 (Broles and identities, family visits, exhibitions as resources for professional development and school visits.s
Keywords: Education; Education; Learning & Instruction